DEVELOPING OF CONCRETE TILES (Journal of Engineering, 2006)
A case study had been made to investigate the reasons of the repetitive failure during concrete tilestesting. Cubes, cylinders, and prisms in addition to full-scale concrete tiles had been prepared. Half of these samples were made using the same popular concrete mix. Test results indicated that, these samples were below standard requirements. The second half of the test samples was prepared using a newly designed concrete mix. Based upon the recommended breaking load, the required flexural strength of the tiles was calculated. This mix was designed to comply a flexural strength that was recommended by specifications. Care had been also concentrated on aggregate grading and concrete curing. Tests showed positive results. In spite of this success it is still believed that there is a possibility of some failures may be due to mass production or due to bad quality control. A new proposed model had been prepared and tested. Finally these newly proposed tiles had shown that it was more resistant to breaking loads by +21% in comparison with the previous samples. This result might insure the production of safe concrete tiles